Measuring the Resilience of Indonesian Islamic Bank Through the RGEC Model - Azhar, Iqlima; Rizka (Asosiasi Dosen Akuntansi Indonesia, 2025)
The purpose of this study is to assess the health of Islamic commercial banks using the RGEC technique, which comprises Risk Profile, Good Corporate Governance, Earnings (Rentability), and Capital. Methods of this study employ a quantitative approach based on secondary data from Islamic Commercial Bank financial reports spanning 2015-2024. In this study, descriptive analysis with the RGEC approach was utilized to determine the health of banks. According to the study's findings, the health of Islamic Commercial Banks from 2015 to 2024 has a composite rating of 1 (PK - 1), placing them in the